2016
DOI: 10.1108/prt-10-2014-0100
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and potential of natural dye colourant from pomegranate (Punica granatum L.)

Abstract: Purpose – The purpose of this paper is to identify the most dominant pigment of pomegranate explants for natural color coatings and detect the presence of phytochemical constituents and comparison of the antioxidant activities. Design/methodology/approach – Extracts of leaf, stem, peel and seed of in vitro and in vivo growth cultures were prepared for phytochemical constituent and antioxidant activity. The supernatant from 95 per cent me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In another work, Mphahlele et al (2016) showed that pomegranate peels had the highest inhibitory activity (with the minimum inhibitory concentration values) against Gram positive bacteria, such as Staphylococcus aureus and Bacillus subtilis. Furthermore, Mohajer et al (2016) have proved that chlorophyll-a extracted from the leaf and stem of pomegranate, can be a potential source of natural colorants for the coating industry and/or as nail varnish.…”
Section: Introductionmentioning
confidence: 99%
“…In another work, Mphahlele et al (2016) showed that pomegranate peels had the highest inhibitory activity (with the minimum inhibitory concentration values) against Gram positive bacteria, such as Staphylococcus aureus and Bacillus subtilis. Furthermore, Mohajer et al (2016) have proved that chlorophyll-a extracted from the leaf and stem of pomegranate, can be a potential source of natural colorants for the coating industry and/or as nail varnish.…”
Section: Introductionmentioning
confidence: 99%
“…In agriculture, PGL aids in preserving animal health by inhibiting feed degradation and combating parasites ( Fathuddin & Inabo, 2017 ; Hassan et al, 2017 ). Manufacturing applications include using PGL as a natural colorant in paints and in petroleum distillate purification and corrosion inhibition ( Abboud et al, 2016 ; Mohajer, Taha, & Azmi, 2016 ; Sadare & Daramola, 2019 ). This comprehensive utilization of PGL highlights its growing versatility and potential across various sectors, suggesting a promising future for PGL-based products and applications (Fig.…”
Section: Current Research and Prospectsmentioning
confidence: 99%
“…Pangestu et al demonstrated that non-acylated anthocyanins such those obtained from Sambucus peruviana and copigmented with ferulic acid could be potentially applied in commercial food products [16]. An improvement of the copigmentation effect was also achieved with pomegranate extract [17]. Anthocyanins as colorants are often used at a low pH, below 4, but some anthocyanin 3-glucosides, such as malvidin 3-glucoside, are relatively stable at a higher pH and can be used for alkaline products [4].…”
Section: Anthocyaninsmentioning
confidence: 99%